2005
DOI: 10.1089/hum.2005.16.479
|View full text |Cite
|
Sign up to set email alerts
|

Gene Transfer to Respiratory Epithelia with Lentivirus Pseudotyped with Jaagsiekte Sheep Retrovirus Envelope Glycoprotein

Abstract: A feline immunodeficiency virus (FIV)-based lentiviral vector was pseudotyped to identify envelope (env) glycoproteins that direct efficient gene transfer to pulmonary epithelia for the treatment or prevention of lung diseases. The envelope glycoprotein from the Jaagsiekte sheep retrovirus (JSRV) is a candidate under investigation. We utilized high titer FIV vector (>10(8) TU/ml) pseudotyped with the JSRV env glycoprotein (JSRVFIV) to study the transduction of polarized primary cultures of human airway epithel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 25 publications
(43 reference statements)
1
27
0
Order By: Relevance
“…Here we confirmed that, as previously reported by us and others (26,30,46), GPI-anchored and soluble forms of Hyal2 are restricted to the apical compartment of airway epithelium, suggesting a specific luminal function, unrelated to the turnover of HA in the bronchial subepithelial tissue.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Here we confirmed that, as previously reported by us and others (26,30,46), GPI-anchored and soluble forms of Hyal2 are restricted to the apical compartment of airway epithelium, suggesting a specific luminal function, unrelated to the turnover of HA in the bronchial subepithelial tissue.…”
Section: Discussionsupporting
confidence: 93%
“…Forms Are Present Apically in NHBE Cells-We and others (26,46) have previously reported that Hyal2 is localized at the apical membrane of the tracheal epithelium. Here we confirmed that Hyal2 is associated with the cell membrane of NHBE cells through a GPI anchor, and limited to the luminal surface (Fig.…”
Section: Gpi-anchored and Soluble Hyal2mentioning
confidence: 93%
“…Lentiviral vectors are well suited for gene transfer because they provide long-term, heritable gene expression by integrating into host cell chromosomes (28). In addition, they can be modified to transduce numerous cell types, including postmitotic neurons and difficult-to-transduce primary neural progenitor cells (NPCs) (9,15,18,23,28,37,38,42). The most well developed lentiviral vector systems are based on human immunodeficiency virus type 1 (HIV-1), and several publications have described delivery of inhibitory RNAs using HIV-1-based lentiviral vectors in vitro and in vivo (20, 22, 26, 32-34, 45, 48).…”
mentioning
confidence: 99%
“…14,18 Recent interest has converged on pseudotyping; be it of adeno-associated virus (AAV)-2 genomes with novel AAV serotypes 21,36 or of integrating lentiviral vectors with viral envelopes from lung pathogens. 28,29,[31][32][33]37 The Ebola virus envelope glycoprotein has been successfully used to pseudotype lentivirus and has achieved efficient transduction of the murine lung epithelium and human explants 33,34 although generation of consistently high viral titres has been problematic. Recently the baculovirus gp64 envelope has been shown to produce significant expression in the nasal epithelia of adult mice up to 1 year after application.…”
Section: Discussionmentioning
confidence: 99%